Effects of dexmedetomidine combined with etomidate on postoperative cognitive function in older patients undergoing total intravenous anaesthesia: a randomized, double-blind, controlled trial - Wuchang Fu; Hongchun Xu; Ting Zhao; Jun Xu; Fangjun Wang (BMC Geriatrics, 2024)
Abstract Background Etomidate has been advocated for anesthesia in older and critically ill patients because of its hemodynamic stability. Clinical studies have shown that dexmedetomidine has neuroprotective and anti-inflammatory properties and improves postoperative cognitive dysfunction in older patients. The present study was to evaluate the effects of the combination of etomidate and dexmedetomidine with different anaesthesia time on postoperative cognitive function in older patients. Methods A total of 132 older patients undergoing ureteroscopic holmium laser lithotripsy were randomly divided into EN group and ED group equally. Patients whose surgery time was less than or equal to 1 h in each group were allocated to short-time surgery group (EN1 group and ED1 group), and whose surgery time was more than 1h were allocated to long-term surgery group (EN2 group and ED2 group). The primary outcome was the score of the Mini-Mental State Examination. The secondary outcomes were State-Trait Anxiety Inventory scores, Riker sedation agitation scores, Zung Self-Rating Depression Scale scores, the memory span for Arabic numerals, the plasma concentrations of S-100 calcium-binding protein B and neuron specific enolase, the time to spontaneous respiration, recovery, and extubation. Results The MMSE scores at t2-3 were higher in ED1 and ED2 groups than in EN1 and EN2 groups (p<0.05). Compared with ED1 and ED2 groups, the ZSDS scores, the S-AI scores and the T-AI scores at t1-2 were higher in EN1 and EN2 groups (p<0.05), respectively. The recalled Arabic numbers at t1-3 were higher in ED2 group than in EN2 group (p<0.05). The plasma concentration of S-100β at t1-2 in EN1 group and t1-3 in EN2 group were higher than that in ED1 and ED2 groups (p<0.05), respectively. Compared with ED1 and ED2 groups, the plasma concentrations of NSE were higher at t1-3 in EN1 group and t1-4 in EN2 group (p<0.05), respectively. Conclusion The administration of dexmedetomidine could improve postoperative cognitive dysfunction, emergence agitation, depression and anxiety, attenuate the plasma concentrations of S-100β and NSE in older patients undergoing total intravenous anaesthesia with etomidate. Trial registration Registration number: ChiCTR1800015421, Date: 29/03/2018.